The influence of light intensity on the performance of FTO/TiO2-ZnO-β carotene-quercetin/carbon/Al/PVDF-BaTiO3/Al photosupercapacitors. (2021) - Diantoro, M.; Masrul, M.Z.; Suprayogi, T.; Ittikhad, A.A.; Himmah, S.W.; Mufti, N.; Aripriharta,; Taufiq, A.; Sunaryono,; Meevasana, W.
Abstract: Exploring new materials and structures and optimizing integrated photosupercapacitors systems are extensively developed. In this work, we report the study of the influence of light intensity on the performance of photosupercapacitors. The photosupercapacitors was constructed from active materials TiO2 -ZnO-natural dye-DSSC and BaTiO3 based supercapacitors. The photoelectric current and open current voltage at various light intensity. The photo-charging was measured under various light intensity illumination 30400, 60800, 91200, 144500, and 170, 800 Lux. It is shown that intensity significantly influences the charging rate on the supercapacitor section. The higher the intensity, the quicker the charging occurs.